Penerapan LKM SURAMI Berbasis Wizer pada Pembelajaran Pemahaman Surat Resmi Murid Kelas VI Sekolah Dasar - Kariima, Layla Faiza; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Instruction in official letter writing at the elementary level has been widely examined, yet studies that specifically integrate Lembar Kerja Murid (LKM) SURAMI based on Wizer to enhance pupils’ understanding of the structure and linguistic features of official letters remain limited. This study aimed to examine the effectiveness of Wizer-based LKM SURAMI in teaching official letter comprehension to sixth-grade pupils at SD IT Insan Mulia Semarang. Adopting a mixed-methods approach with a one-group pretest–posttest design, the research involved 14 pupils selected through total sampling. Data were collected through tests, observations, interviews, and documentation, and were analyzed using descriptive statistics, N-gain calculations, and Miles and Huberman’s qualitative analysis model. The results showed an increase in the mean score from 66 to 86, an improvement in learning mastery from 57.14% to 92.86%, and an N-gain value of 0.60, which falls into the medium category and is interpreted as fairly effective in improving understanding of the structure and linguistic features of official letters. Qualitatively, most pupils were in the “Very Good” category, characterized by focus, enthusiasm, and active engagement during digital worksheet–based learning. These findings enrich the literature on digital literacy and constructivism in the context of Bahasa Indonesia instruction at the elementary level and underscore the potential of Wizer-based LKM SURAMI as an interactive learning medium for optimizing comprehension of formal texts. Follow-up studies are recommended to test the integration of similar digital worksheets in other Bahasa Indonesia topics and in more diverse school settings to obtain a more comprehensive picture of their effectiveness.